Technoeconomic analysis of biogas production using simple and effective mechanistic model calibrated with biomethanation potential experiments of water lettuce (pistia stratiotes) inoculated by buffalo dung. (1st April 2022) - Nahar, Gaurav; Rajput, Shailendrasingh; Grasham, Oliver; Dalvi, Vishwanath Haily; Dupont, Valerie; Ross, Andrew B.; Pandit, Aniruddha B.
Abstract: While many papers report biomethanation potential of various substrates subjected to various treatments, very few report the economic implications of their work. Here, we report a simple but effective mechanistic model, using Contois and Monod kinetics, considering only two classes of micro-organisms (a) acidogens and (b) acetomethanogens. We fitted our model to CH4 and CO2 evolution data from biomethanation studies of water lettuce (pistia stratiotes) inoculated with buffalo dung at five different ratios of substrate to inoculum. The data was obtained by gas chromatography. The model has been used to simulate three types of biodigestors: (a) 1-stage continuous digestor, (b) 2-stage continuous digestor and (c) semi-batch digestor with intermittent draining of digestate. The 2-stage digestor exhibited no major improvement over the 1-stage digestor presenting only a 4% increase in methane production rate with 25% longer response times. The best performance was shown by the semi-batch operation due to tolerance of high microbial loads. Biogas generated from water lettuce grown on a farm pond and using the semi-batch approach can be monetized by offsetting use of market bought LPG. The return on investment is 24.7% and 25 kg of CO2 emissions are abated per ton of water lettuce utilized. Graphical abstract: Image 1 Highlights: Simple, effective mechanistic model using Contois and Monod kinetics for bioreactor design developed. Pistia Stratiotes inoculated with buffalo dung used for biomethanation potential experiments. Model calibrated with CO2 and CH4 evolution data from experiments. Several reactor configurations simulated using the model. Semi-batch 1-stage is optimum configuration, with 24.7% RoI for LPG offset.